Combating youth's unemployment rate by integrating entrepreneurship in middle school education - Antony Fute; Benjamin Remen Mushi; Daniel Kangwa; Mohamed Oubibi (Springer, 2024)
Abstract Entrepreneurship plays a pivotal role in fostering job creation and economic growth, underscoring the need to encourage and support youth in establishing and developing businesses. In Tanzania, where the unemployment rate stands at 2.75% as of 2021, the rising rate (from 2.2% in 2019) necessitates a profound discussion on education for poverty reduction. This study addresses three key questions: (i) from the international experiences, can the entrepreneurship education be effectively integrated into mainstream secondary schools? (ii) What strategies are preferably employed in other countries to integrate entrepreneurship into secondary education? (iii) Based on international experiences, what contextual approach can be adopted by Tanzania to integrate entrepreneurship into middle school education? By employing the PRISMA framework, document review was primarily employed to gain valuable insights. The findings highlighted the importance of teaching entrepreneurship from an early age, recommending strategies such as extracurricular activities, integration of entrepreneurship into related subjects like computer education, and offering it as a stand-alone subject, all while considering contextual factors. Although challenges persist, it is evident that Tanzania's main hurdle in entrepreneurship education and reducing unemployment lies primarily on political willingness rather than financial capacity.